2009
DOI: 10.1024/0300-9831.79.4.230
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Zinc Absorption From Meals: Comparison of Extrinsic Zinc Labeling and Independent Measurements of Dietary Zinc Absorption

Abstract: Background Extrinsic labeling techniques are typically used to measure fractional absorption of zinc (FAZextrinsic) but none have been adequately evaluated. Objective To compare determination of the quantity of zinc absorbed (TAZextrinsic) using measurements of FAZextrinsic with results of simultaneous determinations of dietary zinc absorbed (TAZmetabolic) that are not dependent on labeling ingested food with an extrinsic tracer (modified metabolic balance technique). Design 70Zn was administered orally wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…These latter studies both raised questions in that the methodologies involved quantities of tracer and/or supplemental Zn that constituted a relatively large portion of the total Zn in the test meals. We have recently conducted a study of Zn absorption from whole diets by 21 healthy adult women, which revealed absorption of an extrinsic Zn isotope label and absorption of total Zn in the diets did not differ (P = 0.49) (26). This is consistent with our previous unpublished observations of agreement between Zn absorption measurements using isotopic tracer and metabolic balance methods.…”
Section: Discussionsupporting
confidence: 73%
“…These latter studies both raised questions in that the methodologies involved quantities of tracer and/or supplemental Zn that constituted a relatively large portion of the total Zn in the test meals. We have recently conducted a study of Zn absorption from whole diets by 21 healthy adult women, which revealed absorption of an extrinsic Zn isotope label and absorption of total Zn in the diets did not differ (P = 0.49) (26). This is consistent with our previous unpublished observations of agreement between Zn absorption measurements using isotopic tracer and metabolic balance methods.…”
Section: Discussionsupporting
confidence: 73%
“…Test meals extrinsically labeled (9) with a zinc stable isotope were given for 1 d (study day 1) and with an iron stable isotope for 2 d (study days 1 and 2). Pearl millet was fed daily for a week prior to the metabolic studies, but intake quantities were not recorded.…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
“…As additional total diet data are identified and new data are published that include phytate intake, these data have been added to the original data set of 21 to give a current total of 72 data sets (means) (Figure 2) (6,9,17,18,20,22,24). The parameters of the current model have been compared with the corresponding values for the original model ( Table 1) and indicate further improvement in the certainty of the estimates, which include a lower A MAX .…”
Section: Effect Of Dietary Phytate On the Bioavailability Of Ingestedmentioning
confidence: 99%
“…Measurement of fractional absorption of zinc with isotope, typically stable isotope, techniques is essential to determine the quantity of zinc absorbed and the efficiency of zinc absorption of any quantity of ingested zinc. In our experience, extrinsic labeling with zinc stable isotopes provides a reliable technique to determine the absorption of intrinsic zinc from a wide range of total diets (6).…”
Section: Saturation Response Modeling Of Zinc Absorption Datamentioning
confidence: 99%